Identification of Candidate Genes Downstream of TLR4 Signaling after Ozone Exposure in Mice: A Role for Heat-Shock Protein 70. - Bauer, Alison K.; Rondini, Elizabeth A.; Hummel, Kristin A.; Degraff, Laura M.; Walker, Christopher; Â Jedlicka, AnneÂ E.; Kleeberger, Steven R. (Environmental Health Perspectives, 2011)
BACKGROUND: Toll-like receptor 4 (TLR4) is involved in ozone (O3)-induced pulmonary hyperpermeability and inflammation, although the downstream signaling events are unknown. OBJECTIVES: The aims of our study were to determine the mechanism through which TLR4 modulates O3-induced pulmonary responses and to use transcriptomics to determine potential TLR4 effector molecules. METHODS: C3H/HeJ (HeJ; Tlr4 mutant) and C3H/HeOuJ (OuJ; Tlr4 normal) mice were exposed continuously to 0.3 ppm O3 or filtered air for 6, 24, 48, or 72 hr. We assessed inflammation using bronchoalveolar lavage and molecular analysis by mRNA microarray, quantitative RT-PCR (real-time polymerase chain reaction), immunoblots, immunostaining, and ELISAs (enzyme-linked immunosorbent assays). B6-Hspa1a/Hspa1btm1Dix/NIEHS (Hsp70-/-) and C57BL/6 (B6; Hsp70+/+ wild-type control) mice were used for candidate gene validation studies. RESULTS: O3-induced TLR4 signaling occurred through myeloid differentiation protein 88 (MyD88)-dependent and -independent pathways in OuJ mice and involved multiple downstream pathways. Genomewide transcript analyses of lungs from air- and O3-exposed HeJ and OuJ mice identified a cluster of genes that were significantly up-regulated in O3-exposed OuJ mice compared with O3-exposed HeJ mice or air-exposed controls of both strains; this cluster included genes for heat-shock proteins (e.g., Hspa1b, Hsp70). Moreover, O3-induced inflammation, MyD88 up-regulation, extracellular-signal-related kinase-1/2 (ERK1/2) and activator protein-1 (AP-1) activation, and kerotinocyte-derived chemokine (KC) protein content were significantly reduced in Hspa1a/Hspa1btm1Dix (Hsp70-/-) compared with Hsp70+/+ mice (p < 0.05). CONCLUSIONS: These studies suggest that HSP70 is an effector molecule downstream of TLR4 and is involved in the regulation of O3-induced lung inflammation by triggering similar pathways to TLR4. These novel findings may have therapeutic and preventive implications for inflammatory diseases resulting from environmental exposures.